Effect of maternal prenatal food supplementation, gestational weight gain, and breast-feeding on infant growth during the first 24 months of life in rural Vietnam - Quyen, Phi N.; Nga, Hoang T.; Chaffee, Benjamin; Ngu, Tu; King, Janet C. (PLOS ONE, 2020)
Growth faltering among children during the first five years of life is a common problem among low and middle-income countries. The purpose of this study was to determine the effect of a nutrient-rich, food-based supplement given to Vietnamese rural women prior to and/or during pregnancy on the growth of their infants during first 24 months of life and to identify maternal and newborn factors associated with the infant’s growth. This prospective cohort study included 236 infants born to mothers who had received nutritional advice or a food supplement from pre-conception to term or from mid-gestation to term as part of a prior randomized controlled trial. Infant anthropometry and feeding information were monitored monthly and the infant weight for age Z-score (WAZ), length for age Z-score (LAZ), and weight for length Z-score (WLZ) were assessed at 6, 12, 18, and 24 months of age using mixed-effects regression modeling. Compared to the non-supplemented mothers, infants born to mothers receiving food supplementation from mid-gestation to term had significantly higher WLZ only at 18 months (p = 0.03) and did not differ in other outcomes. Supplementation from pre-conception to term did not affect infant growth at any time point during the first 24 months. In the entire study cohort, maternal height and gestational weight gain were positively associated with the infant’s WAZ and LAZ from 6 to 24 months of age. Programs designed to improve gestational weight gain among women performing demanding physical work throughout a reproductive cycle may improve postnatal infant growth. Trial registration: Registered Clinical Trials.Gov: NCT01235767.